Brain biomarkers and neuropsychological outcomes of pediatric posterior fossa brain tumor survivors treated with surgical resection with or without adjuvant chemotherapy. Issue 2 (29th November 2020) - Baron Nelson, Mary C.; O'Neil, Sharon H.; Tanedo, Jeffrey; Dhanani, Sofia; Malvar, Jemily; Nuñez, Christopher; Nelson, Marvin D.; Tamrazi, Benita; Finlay, Jonathan L.; Rajagopalan, Vidya; Lepore, Natasha
Abstract: Purpose: Children with brain tumors experience cognitive late effects, often related to cranial radiation. We sought to determine differential effects of surgery and chemotherapy on brain structure and neuropsychological outcomes in children who did not receive cranial radiation therapy (CRT). Methods: Twenty‐eight children with a history of posterior fossa tumor (17 treated with surgery, 11 treated with surgery and chemotherapy) underwent neuroimaging and neuropsychological assessment a mean of 4.5 years (surgery group) to 9 years (surgery + chemotherapy group) posttreatment, along with 18 healthy sibling controls. Psychometric measures assessed IQ, language, executive functions, processing speed, memory, and social‐emotional functioning. Group differences and correlations between diffusion tensor imaging findings and psychometric scores were examined. Results: The z ‐score mapping demonstrated fractional anisotropy (FA) values were ≥2 standard deviations lower in white matter tracts, prefrontal cortex gray matter, hippocampus, thalamus, basal ganglia, and pons between patient groups, indicating microstructural damage associated with chemotherapy. Patients scored lower than controls on visuoconstructional reasoning and memory ( P  ≤ .02). Lower FA in the uncinate fasciculus ( R  = −0.82 to −0.91) and higher FA in the thalamus ( R  = 0.73‐0.91) associated with higher IQ scores, and higher FA in the thalamus associated with higher scores on spatial working memory ( R  = 0.82). Conclusions: Posterior fossa brain tumor treatment with surgery and chemotherapy affects brain microstructure and neuropsychological functioning years into survivorship, with spatial processes the most vulnerable. Biomarkers indicating cellular changes in the thalamus, hippocampus, pons, prefrontal cortex, and white matter tracts associate with lower psychometric scores.